Bending performance evaluation of aluminium alloy tubes filled with different cellular metal cores. (15th February 2020) - Vesenjak, Matej; Duarte, Isabel; Baumeister, Joachim; Göhler, Hartmut; Krstulović-Opara, Lovre; Ren, Zoran
Abstract: A comprehensive bending performance and energy absorption capability of aluminium alloy tubes filled with different cost-effective cellular metal cores were experimentally evaluated for the first time. The following cellular metal cores were evaluated: i) Advanced Pore Morphology (APM) foam, ii) hybrid APM foam and iii) Metallic Hollow Sphere Structures (MHSS). The results have been compared also with the performance of aluminium alloy tubes filled with ( ex-situ and in-situ ) closed-cell aluminium alloy foam. The three-point bending tests have been performed at two loading rates (quasi-static and dynamic) and supported by infrared thermography to evaluate the deformation mechanism, damage progress and failure modes. A thorough heat treatment sensitivity (due to the fabrication procedures of composite structures) study on the aluminium tubes has been performed as well. The results show that a reliable and predictable mechanical behaviour and failure can be achieved with proper combination of tubes and cellular metal core. A low scatter of bending properties and energy absorption capability has been observed. The hybrid APM and the ex-situ foam filled tubes achieved the highest peak load. However, they also exhibit a rapid load drop and abrupt failure once the structure has reached the peak load. The APM, MHSS and in-situ foam filled tubes show more ductile behaviour with a predictable failure mode.